Foreign direct investment-economic growth nexus:the role of domestic financial development in Portugal - Shahbaz, Muhammad (2011)
The aim of present paper is to examine the role of financial development on FDI-Growth nexus using annual data over the period of 1975-2008. The results show that financial development is playing its role well but not satisfactory. This study will provide new guidelines for policy making authorities for Portuguese's economy. The manuscript applies the unrestricted error correction model (ECM) estimator advanced by Inder (1993) while ARDL bounds testing approach is employed to find cointegration among variables. Stationarity issue is investigated by Ng-Perron unit root test. The results show that financial development stimulates economic growth for the case of Portugal. Foreign direct investment also good promoter of economic growth while investment in public capital stock is contributing more as compared to financial development and foreign direct investment. Inflation declines economic growth.